Brhat Kurāḷa purāṇa - Dīnakrshṇa Dāsa, d. ca. 1715 (Dharmagrantha Shṭora, 1970)
Verse work, in puranic style, describing the mythical origin and history of the Kurāḷas (Kumhars) Hindu pottery craftsmen.